Hip arthroplasty with use of cement technologies and radiological assessment of the state of implants - Loskutov, Oleg; Vasilchenko, Yegor (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2014)
The article analyses radiographs of 59 patients after hip arthroplasty with use of cement technologies. The authors revealed the main radiological indices, which affected the result of surgical interventions. The placement of endoprosthesis components and the state of the cement mantle were assessed by the Charnley-DeLee and Gruen zones, and the degree of the medullary canal filling by Barrack’s grading system. The radiological assessment of the performed cement arthroplasty of the hip joint makes it possible to check the quality of the surgical intervention made, prognosticate the duration of the endoprosthesis functioning and diagnose aseptic instability of the implant in time.